Effect of Salvia sclarea L. extract on growth performance, antioxidant capacity, and immune function in lambs - Ma, Xiaoling; Niu, Yujie; Nan, Shanshan; Zhang, Wenju (Frontiers in Veterinary Science, 2024)
Effect of Salvia sclarea L. Extract on growth performance, antioxidant capacity and immune function in lambs